A treat-to-target strategy with methotrexate and intra-articular triamcinolone with or without adalimumab effectively reduces MRI synovitis, osteitis and tenosynovitis and halts structural damage progression in early rheumatoid arthritis: results from the OPERA randomised controlled trial. Issue 5 (10th January 2014) - Axelsen, Mette Bjørndal; Eshed, Iris; Hørslev-Petersen, Kim; Stengaard-Pedersen, Kristian; Hetland, Merete Lund; Møller, Jakob; Junker, Peter; Pødenphant, Jan; Schlemmer, Annette; Ellingsen, Torkell; Ahlquist, Palle; Lindegaard, Hanne; et al.
Abstract : Objectives: To investigate whether a treat-to-target strategy with methotrexate and intra-articular glucocorticosteroid injections suppresses MRI inflammation and halts structural damage progression in patients with early rheumatoid arthritis (ERA), and whether adalimumab provides an additional effect. Methods: In a double-blind, placebo-controlled trial, 85 disease-modifying antirheumatic drug-naïve patients with ERA were randomised to receive methotrexate, intra-articular glucocorticosteroid injections and placebo/adalimumab (43/42). Contrast-enhanced MRI of the right hand was performed at months 0, 6 and 12. Synovitis, osteitis, tenosynovitis, MRI bone erosion and joint space narrowing (JSN) were scored with validated methods. Dynamic contrast-enhanced MRI (DCE-MRI) was carried out in 14 patients. Results: Synovitis, osteitis and tenosynovitis scores decreased highly significantly (p<0.0001) during the 12-months' follow-up, with mean change scores of −3.7 (median −3.0), −2.2 (−1) and −5.3 (−4.0), respectively. No overall change in MRI bone erosion and JSN scores was seen, with change scores of 0.1 (0) and 0.2 (0). The tenosynovitis score at month 6 was significantly lower in the adalimumab group, 1.3 (0), than in the placebo group, 3.9 (2), Mann–Whitney: p<0.035. Furthermore, the osteitis score decreased significantly during the 12-months' follow-up in the adalimumab group, but not in the placebo group, Wilcoxon: p=0.001–0.002 and p=0.062–0.146. DCE-MRI parameters correlated closely with conventional MRI inflammatory parameters. Clinical measures decreased highly significantly during follow-up. Conclusions: A treat-to-target strategy with methotrexate and intra-articular glucocorticosteroid in patients with ERA effectively decreased synovitis, osteitis and tenosynovitis and halted structural damage progression as judged by MRI. The findings suggest that addition of adalimumab is associated with further suppression of osteitis and tenosynovitis.